Characteristics and prediction of permian tight glutenite reservoirs in dinan 15 well block, junggar basin - Wei, Xin; Sun, Xinming; Yuan, Xuejiao; Yang, Yiming (Frontiers in Earth Science, 2022)
Glutenite reservoirs are characterized by rapid lateral change, strong heterogeneity, and complex main controlling factors. This research aims to identify macro and micro characteristics of glutenite reservoirs and establish criteria for identifying favorable reservoirs studies. To this end, the tight sandy conglomerate of the Upper Wuerhe Formation in the Permian Upper Wuerhe Formation in the Dinan 15 well area of the eastern slope of the Dongdaohaizi sag in the Junggar Basin is studied. The core observation, physical property analysis, sensitivity analysis, casting thin section, scanning electron microscope and logging data are adopted to comprehensively analyze the characteristics of glutenite reservoirs. By integrating various reservoir characteristic parameters, this work constructed a new set of reservoir evaluation criteria to predict favorable areas for the Upper Wuerhe Formation in Dongdaohaizi Sag. The results show that the lithology of the Upper Wuerhe Formation in the Dinan 15 well area is dominated by gray glutenite; the reservoir is an ultra-low porosity and ultra-low permeability reservoir with moderately weak water sensitivity and weak velocity sensitivity. The reservoir space types of the layers are mainly intergranular pores; the shape of the mercury intrusion curve and the pore throat radius distribution of the samples show that the reservoir is skewed, poorly sorted, and has the characteristics of small pores and thin throats. This work constructed evaluation criteria for reservoirs from I to III by utilizing lithology, physical properties, sensitivity, reservoir space type, and microstructural characteristics as key parameters. The favorable reservoir distribution area is mainly located in the west of the block, which is the focus of the next exploration of the Upper Wuerhe Formation area. The research results improved understanding of glutenite reservoir characteristics and will serve as significant guidance for the oil and gas exploration in the Dinan 15 well area.